2021
DOI: 10.1002/cctc.202100692
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the Zn‐Cu Interaction during Activation of a Zn‐promoted Cu/MgO Model Methanol Catalyst

Abstract: We report on an inverse model Cu/MgO methanol catalyst modified with 5 % zinc oxide at the Cu surface to element‐specifically probe the interplay of metallic copper and zinc oxide during reductive activation. The structure of copper and zinc was unraveled by in situ X‐ray diffraction (XRD) and in situ X‐ray absorption spectroscopy (XAS) supported by theoretical modelling of the extended X‐ray absorption fine structure and X‐ray absorption near‐edge structure spectra. Temperature‐programmed reduction in H2 duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 63 publications
3
30
0
Order By: Relevance
“…A peak at 2.2 Å in the FT‐region developed for both catalysts, indicating some brass alloying for both catalysts at 230 °C (Figure 7). [32] …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A peak at 2.2 Å in the FT‐region developed for both catalysts, indicating some brass alloying for both catalysts at 230 °C (Figure 7). [32] …”
Section: Resultsmentioning
confidence: 99%
“…We have also recently reported that only ZnO that is in direct contact with copper and able to form a surface CuÀ Zn alloy can be reduced. [32] Its fraction is low both for CZA and CZG.…”
Section: Temperature-programmed Reduction Of Czg and Cza Methanol Syn...mentioning
confidence: 96%
See 1 more Smart Citation
“…Reduction of bulk ZnO occurs only at higher temperatures, but the baseline drift starting at 350 °C can be assigned to the start of the ZnO reduction (ZnO domains in interaction with Cu) and the decomposition of a residual carbonate phase. 39 , 40 The quantification of the TPR profile reveals that all Cu(II) was reduced, with a H 2 /M molar ratio of 1.16. The higher value than unity is due to the partial reduction of ZnO; ZnO species in close interaction with Cu can form a Cu–Zn brass.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the role of Zn may also be considered as it has been claimed as having a role in the active site for methanol synthesis. 40 , 46 , 55 57 …”
Section: Resultsmentioning
confidence: 99%